Me, Myself, and Not-I: Self-Discrepancy Type Predicts Avatar Creation Style - Loewen, Mitchell G. H.; Burris, Christopher T.; Nacke, Lennart E. (Frontiers in Psychology, 2021)
In video games, identification with avatars—virtual entities or characters driven by human behaviour—has been shown to serve many interpersonal and intraindividual functions (like social connection, self-expression, or identity exploration) but our understanding of the psychological variables that influence players’ avatar choices remains incomplete. The study presented in this paper tested whether players’ preferred style of avatar creation is linked to the magnitude of self-perceived discrepancies between who they are, who they aspire to be, and who they think they should be. One-hundred-and-twenty-five undergraduate gamers indicated their preferred avatar creation style and completed a values measure from three different perspectives: their actual, ideal, and ought selves. The average actual/ideal values discrepancy was greater among those who preferred idealized avatars versus those who preferred realistic avatars. The average actual/ought values discrepancy was greater among those who preferred completely different avatars (i.e., fantasy/role-players) versus those who preferred realistic avatars. These results, therefore, offer additional evidence that self-discrepancy theory is a useful framework for understanding avatar preferences.